Deep nerve ultrasonic automatic positioning and mapping method, device, equipment and medium - XIAO YANG (2022)
The invention discloses a deep nerve ultrasonic automatic positioning and mapping method, which comprises the following steps of: covering a multi-array-element ultrasonic array transducer above a to-be-positioned target region of a subject, and then driving the multi-array-element ultrasonic array transducer to emit multiple paths of ultrasonic waves, and focusing at any preset detection position of the to-be-positioned target region in the human body to form a focus so as to provide ultrasonic stimulation, and acquiring corresponding stimulation response data at the to-be-positioned nerve-related action part. In this way, the probe can be prevented from being moved, the target area can be automatically and completely scanned only by adjusting the position of the focus formed by focusing, and therefore the coupling performance with the human body is improved. Then, in the obtained multiple pieces of stimulation response data, the corresponding preset detection position with the stimulation response data larg